The role of HEPCAM in Jacobsen syndrome: A pediatric case report highlighting white matter abnormalities - Ghazaleh Ghorbannezhad; Reza Nejad Shahrokh Abadi; Farrokh Seilanian Toosi; Shima Shekari; Saeedeh Sadat Mirtooni; Narges Hashemi (Brain Disorders)
Jacobsen syndrome (JS) is a rare contiguous gene deletion disorder characterized by a deletion at the terminal end of the long arm of chromosome 11. JS has various phenotypic features, such as neurodevelopmental delays and congenital heart defects. Furthermore, deletion mutations in the long arm of chromosome 11 can also give rise to Megalocephalic Leukoencephalopathy (MLC), affecting the HEPCAM gene. The following case report presents a 9-year-old girl with JS and remarkable white matter abnormalities (WMA). Despite the complex clinical presentation with craniofacial anomalies and limb malformations, there were slow partial improvements in the WMAs over time as evidenced by sequential MRI findings. This case adds to the previously documented literature on the topic of white matter abnormalities in the context of Jacobsen syndrome, and showcases these changes after several years.